Double Tongue Appearance of Congenital Neck Mass: Successful Management of Restricted Airway with Awake Fiberoptic Nasal Intubation - Khalid, Atif; Nasreen, Farah; Kumar, Manish (ENT Updates, 2024)
Epidermoid cysts are benign lesions that can cause mechanical airway obstruction if present in the neck and extend into the mouth foor. A 30-year-old male patient presented with a large, painless swelling in the anterior aspect of the neck and mouth foor. Surgical excision was planned under general anesthesia, and awake nasal fberoptic intubation was the sole choice in view of restricted oral space secondary to swelling. This case report highlights the importance of planned awake nasal fberoptic intubation and the challenges involved in the airway management of such rare cases.